Clinico-biochemical relation of Vitamin D3 with the severity of atopic dermatitis and response to supplementation of Vitamin D3: A randomized controlled trial - Modi, Narayan Prasad; Dash, Arun Kumar (Indian Journal of Child Health, 2021)
Background: Atopic dermatitis (AD), also known as eczema, is one of the most common skin disorders among children and adults, with a steep rise in diagnoses among children. Many studies have investigated the relationship between Vitamin D3 (Vit D3) and AD. Methods: A randomized controlled trial was conducted among 60 children at SCB Medical College, Cuttack from August 2014 to November 2016. Children were randomly assigned to an intervention group that received 60,000 IU of Vit. D3 every week for 6 weeks in addition to regular treatment for AD and a control group that received same treatment of AD except for Vit. D3. Both the groups were followed up at 4 weeks and 8 weeks. Results: In 60 cases of moderate to severe AD, 70% of the patients were male. About 81.7% of patients were from urban areas and 56.7% belonged to a middle socioeconomic class. In 76.6% of cases, family history of atopy was present. At baseline, mean SCORAD was 47.8±7.5 in the intervention group, and 49.2±10.3 in the control group. At baseline, serum Vitamin. D3 level (ng/ml) was 17.6±1.8 in intervention and 17.3±3.5 in control group. After Vitamin. D3 supplementation, the SCORAD improved to 12.8±5.1 (75% reduction) at 4 weeks, and 3.6±2.1 (92% reduction) at 8 weeks in the intervention group. In the control group, the mean SCORAD was 18.8±9.1 (61% reduction) at 4 weeks, and 7.3±4 (85% reduction) at 8 weeks. Discussion: The improvement of serum 25-hydroxy Vit. D3 was 134% and 366% in the intervention group compared to 78% and 121% in the observation group after 4 weeks and 8 weeks respectively. The p-values at both the time points were significant (<0.05) for the intervention group as compared to the control group. Conclusion: Short-term therapeutic supplementation of Vitamin. D3 in children with moderate to severe AD improves the clinical score. There is an inverse relationship between serum Vitamin. D3 level and severity of AD.